1981
DOI: 10.1258/002367781780893740
|View full text |Cite
|
Sign up to set email alerts
|

Lethal pneumonia in guineapigs associated with a virus

Abstract: No bacteria were observed in an epizootic of lethal pneumonia in guineapigs. Necrotic bronchitis and bronchiolitis with basophilic intranuclear inclusion bodies in bronchial epithelial cells were characteristic. Although adenovirus infection of guineapigs has not previously been reported, histological findings paralleled those found in adenovirus infections of other animals including man. Virus particles found by electron-microscopical examination of the lung tissue closely resembled adenoviruses. The disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
3

Year Published

1983
1983
2017
2017

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 8 publications
0
9
0
3
Order By: Relevance
“…Although a variety of viral diseases do occur in the guinea pig, there has been only one previous report of cavian respiratory disease associated with what was believed to be an adenovirus [6] and none reported in the U.S. We report here two cases of pneumonia associated with a virus morphologically similar to adenovirus.Two adult, female Hartley Crl:(HA/BR) guinea pigs being used in anthrax vaccine trials showed clinical signs of hunched posture, weight loss, rough hair coat, rapid labored breathing, and a catarrhal exudate around the external nares and on the front feet. Guinea pig 1 had received five injections of an experimental anthrax vaccine at two-day intervals, while guinea pig 2, as part of the control group, had received five saline injections at the same intervals.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Although a variety of viral diseases do occur in the guinea pig, there has been only one previous report of cavian respiratory disease associated with what was believed to be an adenovirus [6] and none reported in the U.S. We report here two cases of pneumonia associated with a virus morphologically similar to adenovirus.Two adult, female Hartley Crl:(HA/BR) guinea pigs being used in anthrax vaccine trials showed clinical signs of hunched posture, weight loss, rough hair coat, rapid labored breathing, and a catarrhal exudate around the external nares and on the front feet. Guinea pig 1 had received five injections of an experimental anthrax vaccine at two-day intervals, while guinea pig 2, as part of the control group, had received five saline injections at the same intervals.…”
mentioning
confidence: 71%
“…Although a variety of viral diseases do occur in the guinea pig, there has been only one previous report of cavian respiratory disease associated with what was believed to be an adenovirus [6] and none reported in the U.S. We report here two cases of pneumonia associated with a virus morphologically similar to adenovirus.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…I). Under natural conditions the disease was evident only in compromised animals used for such related studies as tuberculosis diagnosis (Naumann, Kunstyf, Langer, Maess & Horning, 1981 (Figs 4 and 5), the resistance to ether, along with the observations on the course of the disease, the pathological and ultrastructural changes in the lungs (Naumann, Kunstyr, Langer, Maess & Horning, 1981;Kaup, Naumann, Kunstyf & Drommer, in preparation), and the difficulties of in vitro cultivation we assume that the aetiological agent is an adenovirus as described by Andrews, Pereira & Wildy (1978).…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus-induced respiratory disease with low morbidity and high mortality has been documented in guinea pigs [20][21][22][23][24]. Clinical signs range from those of pneumonia, including dyspnea, tachypnea, nasal discharge, rough hair coat, weight loss, and a hunched posture to acute death with no clinical signs.…”
Section: Respiratory Disease In Guinea Pigsmentioning
confidence: 99%